Network security foundations - Strebe, Matthew (Technology fundamentals for IT success, 2006)
The world of IT is always evolving, but in every area there are stable, core concepts that anyone just setting out needed to know last year, needs to know this year, and will still need to know next year. The purpose of the Foundations series is to identify these concepts and present them in a way that gives you the strongest possible starting point, no matter what your endeavor. Network Security Foundations provides essential knowledge about the principles and techniques used to protect computers and networks from hackers, viruses, and other threats. What you learn here will benefit you in the short term, as you acquire and practice your skills, and in the long term, as you use them. Topics covered include: Why and how hackers do what they do How encryption and authentication work How firewalls work Understanding Virtual Private Networks (VPNs) Risks posed by remote access Setting up protection against viruses, worms, and spyware Securing Windows computers Securing UNIX and Linux computers Securing Web and email servers Detecting attempts by hackers